Hotplace Magnetic Stirrer Automatic Heat Control and Water Velocity Based on PID (Proportional Integral Derivative) - Zaifuddin; Achmad Ibadillah; Riza Alfita; Deni Tri Laksono (Procedia of Engineering and Life Science, 2021)
Hotplate magnetic stirrer is a laboratory tool that is used to heat or warm as well as mix or homogenize chemical solutions. This tool is available in chemical, microbiology and pharmaceutical laboratories. Equipped with a stirrer made of magnets (stir bar) which is used to homogenize chemical solutions. This magnetic stirrer hotplate uses an ATMega 16 microcontroller based system. It uses an infrared temperature sensor MLX90614 to measure and monitor the temperature of the solution, starting from the start of mixing which is assisted by rotating a DC motor as a stirring device until the liquid is mixed or homogeneous. Homogeneous conditions are indicated by the ADC value ( Analog to Digital Convertion) which is obtained constant. If you use the automatic menu, only choose the mixing solution on the automatic menu. There are four choices for the solution speed of 400-1600 rpm with an increase of 400, there are four temperature choices, namely 30-60 degrees Celsius in increments of 10, there is a choice of time used for stirring time at 1-30 minutes. For temperature display, stirring speed and stirring time can be seen on the LCD 20x4 display.